Efficiency of four Malaysian commercial disinfectants on removing Listeria monocytogenes biofilm - Fouladynezhad, Nina; Afsah Hejri, Leili; Rukayadi, Yaya; Nakaguchi, Yoshitsugu; Nishibuchi, Mitsuaki; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Listeria monocytogenes(L. monocytogenes) is a gram positive food-borne pathogen that is able to form biofilm on food factory surfaces. Formation of biofilm makes the bacteria much more resistance to environmental stresses such as disinfectant. The extracellular polymeric matrix (biofilm structure) which is mostly comprised of sticky extracellular polysaccharides (EPS) and proteins can protect bacteria in a harsh condition. The efficiency of four disinfectants on removing L. monocytogenes biofilm was investigated. Five concentration levels (100, 50,25, 12.5, and 6.25%) of disinfectants were tested. In the microtitre assay, the optical density at 595 nm CV-OD 595 value, was used to measure the amount of remained biofilm after 24 h. Results showed that disinfectants did not have significant effect on removing L. monocytogenes biofilm. Formation of L. monocytogenes biofilm significantly decreased the efficiency of disinfectants. Biofilm produced by strain number 9 showed higher resistance to disinfectant. Low concentrations (<50%) of disinfectants did not show significant effect on removing L. monocytogenes biofilm.